ANALISIS LOCATION QUOTIENT PADA SEKTOR TANAMAN SAYURAN DI KABUPATEN NGAWI - Dhandy, Rahmat; Brillyantina, Septine; Mutmainah, Dini Nafisatul; Rahmawati, Elis; Solihah, Mar’atus (Program Studi Agribisnis Fakultas Pertanian, 2024)
The agricultural sectors that are developed should be sectors that have a major contribution to economic growth in Ngawi Regency. The aim of this research is to analyze which sectors have priority development in Ngawi Regency. This needs to be done so that subsectors that have the potential for the progress of vegetable crops in the region can be optimized. In this way, regions can find out about economic progress as a result of development in the agricultural sector in their region. This research analyzes the contribution of the basic vegetable subsector to the economic growth of the agricultural sector in Ngawi Regency. This analysis can help the government in setting policies regarding the economy and regional development so that it is hoped that community welfare will be created in Ngawi Regency. The research was carried out in August-October 2024, located in 19 sub-districts in Ngawi Regency. The highest LQ value is cayenne pepper which is found in 12 (twelve) sub-districts, namely Sine sub-district LQ value 3.09, Ngrambe sub-district LQ value 3.04, Jogorogo sub-district LQ value 2.94, Geneng sub-district LQ value 3.10, Gerih sub-district LQ value 6.53, Kwadungan sub-district LQ value 2.12, Paron District LQ value 3.69, Kedunggalar District LQ value 13.72, Pitu District LQ value 1.73, Widodaren District LQ value 22.26, Mantingan District LQ value 13.97 and Karanganyar District LQ value 4.49. This illustrates that cayenne pepper is a basic sector where farmers are generally able to make good use of the available land.